Model of a Low-Cost Educational Prototype of the Furuta Pendulum - Martínez Ramírez, Emmanuel; Diaz Ledezma, Marcelino Alan; López Portillo Zuarth, David; Vicente Ortiz, Alex Yoel; Mera Sánchez, Nelson Rosendo; Ordaz Oliver, Mario Oscar; Espejel Rivera, María Angélica (International Journal of Combinatorial Optimization Problems and Informatics, 2025)
Didactic control systems are tools that facilitate the understanding of topics related to control and stabilisation. However, due to the high cost of these devices, their implementation in schools is limited. This work presents the design, construction, and testing of a low-cost didactic prototype of a Furuta-type pendulum for the analysis of topics related to this system. The construction included parts designed in SolidWorks and produced with 3D printing, threaded rods, a precision linear potentiometer, a DC motor, a BTS7960 H-bridge, and an Arduino Nano. The functionality of the project was verified through the implementation of two digital tools: a Kalman filter to improve the measured signal and a PID controller to regulate the angular speed of the motor. It was demonstrated that the prototype can be stabilised under the operational considerations of PID control without the use of an angular position sensor. Moreover, the Kalman filter must be kept small in order to avoid information loss.